HUBUNGAN PENGETAHUAN ORANG TUA DENGAN KEBERSIHAN GIGI DAN MULUT PADA ANAK TUNAGRAHITA KELAS I-VI DI SEKOLAH LUAR BIASA (SLB) NEGERI KOTA BANJARBARU - Farihah Farihah; Siti Salamah; Anderi Fansurna (JURNAL TERAPIS GIGI DAN MULUT, 2021)
Parental knowledge in guiding becomes one of the factors in handling oral and dental hygiene and also greatly affects the oral and dental hygiene of mentally retarded children. Preliminary survey conducted by researchers on mentally retarded children grade I-VI in the Special School (SLB) Negeri Banjarbaru City known the average value of dental and oral hygiene of 3.2 out of 6 children who have been examined with poor and average OHI-S criteria the parents of the child cannot answer correctly. The purpose of this study was to determine the relationship of parental knowledge with oral and dental hygiene in retarded children in grades I-VI in the Special School (SLB) Negeri Banjarbaru City. This type of research is analytic with Cross Sectional approach, the total sample of 35 mentally retarded children and 35 parents. Data were processed and analyzed using the Chi Square test. The results of the study of parental knowledge are mostly not good and most of the oral and dental hygiene in children with intellectual disabilities. The test results on Chi Square obtained p-values ​​seen in Asymp. Sig. (2-sided) = 0,000, so the p-value is calculated ˂ p-value alpha (0.05) so that Ho is rejected and Ha is accepted. The conclusion is that there is a relationship between parents' knowledge and oral and dental hygiene in retarded children in grades I-VI at the Banjarbaru City Extraordinary School (SLB). The suggestion is to increase parents 'knowledge about oral and dental hygiene to include parents in UKGS activities in the form of education about oral health so that parents' knowledge about oral and dental hygiene increases. Keywords: Parental knowledge, oral and dental hygiene, retarded children